2015
DOI: 10.1111/1754-9485.12422
|View full text |Cite
|
Sign up to set email alerts
|

CT perfusion in acute stroke calls: A pictorial review and differential diagnoses

Abstract: SummaryCT perfusion is increasingly utilised in hyperacute stroke to facilitate diagnosis and patient selection for reperfusion therapies. This review article demonstrates eight examples of how CT perfusion can be used to diagnose stroke mimics and small volume infarcts, which can be easily missed on non-contrast CT, and to suggest the presence of an ischaemic penumbra. Radiologists involved in stroke management must understand the importance of rapid imaging acquisition and be confident in the prospective int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…EVT is offered as adjunctive treatment to alteplase if the CT angiographic image identifies a LVO in the anterior circulation, and if the CT perfusion scan identifies a salvageable penumbra (increased time to peak) surrounding any core infarction (decreased cerebral blood volume) [5]. Patients proceed to EVT while the alteplase infusion is in progress.…”
Section: Methodsmentioning
confidence: 99%
“…EVT is offered as adjunctive treatment to alteplase if the CT angiographic image identifies a LVO in the anterior circulation, and if the CT perfusion scan identifies a salvageable penumbra (increased time to peak) surrounding any core infarction (decreased cerebral blood volume) [5]. Patients proceed to EVT while the alteplase infusion is in progress.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the major technological advances in neuroimaging, the diagnostic accuracy and prognosis of stroke have improved dramatically in the past few decades. However, imaging studies are limited by low sensitive to infarction in the first 2 hrs and unavailability in limited-resource areas 11. Thus, innovative diagnostic tools and biomarkers have been proposed including acute phase reactants, IL-6, and microRNAs (miRNA) 12…”
Section: Introductionmentioning
confidence: 99%
“…The parieto-occipital lobes seem to be more likely involved in PRES, although involvement of other regions of the brain is possible. [60][61][62][63] Perfusion imaging alterations in patients diagnosed with PRES are inconsistent among studies. While some studies found a hypoperfusion pattern characterized by decreased CBF and CBV and delayed MTT and Tmax, 62,64 others showed hyperperfusion with increased CBF and CBV and decreased MTT and Tmax in patients with PRES (Figure 4).…”
Section: Posterior Reversible Encephalopathy Syndromementioning
confidence: 99%